Spray-pyrolysed tin doped zinc oxide thin films-analysis based on microstructural, optical and morphological characterizations - V.K. Devanarayanan; S. Deepa; J. Jassi; Arshad Salim (Results in Surfaces and Interfaces)
Tin (Sn) doped Zinc oxide (ZnO) thin films are prepared via spray pyrolysis technique at varying doping concentrations. X-Ray diffraction (XRD) studies confirm the hexagonal wurtzite phase of the prepared samples. The crystallite size of the samples lies between 40 and 60 nm. The Field Emission Scanning Electron Microscope (FESEM) is used to investigate the morphological aspects. UV–Visible Absorbance spectra reveal a variation of band gap from 3.21 to 3.28 eV. The sub-stoichiometric phase and oxygen vacancies in the samples have been examined using Raman spectra and verified by photoluminescence spectra. The results confirm that a moderate level of Sn doping enhances the CO2 sensing performance of ZnO thin films.